Comparative study of artificial light plant factories and greenhouse seedlings of SAOPOLO tomato - Jun Zou; Wenbin Liu; Dawei Wang; Shipeng Luo; Shaojun Yang; Xiaotao Ding; Mingming Shi (PLoS ONE, 2025)
In the summer, the high temperatures, high humidity, frequent rainstorms, and typhoons in the East China region limit the growth of SAOPOLO tomato seedlings. By using a plant factory combined with an LED artificial light environment, the light environment can be effectively controlled to produce high-quality seedlings. This study investigates the growth and energy consumption of tomato seedlings in an artificial light plant factory. The experiment compared tomato seedlings cultivated in the artificial LED light environment of a plant factory with those grown in a semi-enclosed seedling greenhouse. The study meticulously examined the actual growth and development processes of the tomato seedlings, systematically tracking and recording the specific impacts of different cultivation environments on the seedlings’ growth and development. Additionally, the experiment followed up on the fruiting conditions of the subsequent tomato plants. The experimental results show that compared to tomato seedlings grown in a greenhouse, those cultivated in the artificial light plant factory grew more slowly before grafting, characterized by slightly lower plant height, relatively smaller leaf area, and slightly thinner stems. However, after grafting, the growth rate of the tomato seedlings in the plant factory significantly accelerated, with increased plant height, leaf area, and stem diameter. On the 16th day after grafting, the cumulative leaf length and width fitting curves for the two cultivation methods coincided. Furthermore, it is noteworthy that the electricity consumption during the tomato seedling cultivation process, including that for controlling environmental temperature and humidity and the LED artificial supplemental lighting in the plant factory, was significantly lower. Over the two-month seedling cultivation period, the resource consumption in the greenhouse was 220% and 281% higher than in the plant factory, respectively. Statistical results also showed that the mortality rate of tomato seedlings cultivated in the artificial light plant factory was only 4.3%, much lower than the 6.5% mortality rate in the greenhouse. When the subsequent tomato plants were uniformly transplanted to the greenhouse for cultivation and their fruit weights were measured and recorded, the results indicated no significant difference in the fruit weights of tomatoes grown in the plant factory compared to those grown in the greenhouse. Therefore, experimental evidence confirms that cultivating tomato seedlings in an artificial light plant factory can significantly reduce cultivation costs, increase seedling survival rates, and not affect tomato quality.